2008
DOI: 10.1080/00223890802388590
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Structure of the Narcissistic Personality Inventory

Abstract: In the first study, we administered the 40-item Narcissistic Personality Inventory (NPI; Raskin & Terry, 1988) to 843 female and 843 male college students, most of whom were Euro-American, to comprehensively assess the NPI factor structure using confirmatory factor analysis. Initial exploratory common factor analyses (N = 724) revealed a 2-factor model (Leadership/Authority and Exhibitionism/Entitlement). Subsequently, we used confirmatory factor analysis in a separate sample (N = 724) to evaluate the Emmons (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
201
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(228 citation statements)
references
References 24 publications
16
201
0
6
Order By: Relevance
“…Narcissism was assessed with the Narcissistic Personality Inventory (NPI; Raskin & Hall, 1979; for the German version, see Schütz et al, 2004), using the 16-item short form suggested by Ames, Rose, and Anderson (2006). The NPI is the most frequently used and well-validated measure of narcissism (Ackerman et al, 2011;Corry, Merritt, Mrug, & Pamp, 2008;Emmons, 1987;Raskin & Terry, 1988). The NPI uses a forced-choice response format;…”
Section: Methodsmentioning
confidence: 99%
“…Narcissism was assessed with the Narcissistic Personality Inventory (NPI; Raskin & Hall, 1979; for the German version, see Schütz et al, 2004), using the 16-item short form suggested by Ames, Rose, and Anderson (2006). The NPI is the most frequently used and well-validated measure of narcissism (Ackerman et al, 2011;Corry, Merritt, Mrug, & Pamp, 2008;Emmons, 1987;Raskin & Terry, 1988). The NPI uses a forced-choice response format;…”
Section: Methodsmentioning
confidence: 99%
“…Factor analyses of the NPI have found from two to seven factors (Ackerman et al, 2011;Corry, Merritt, Mrug, & Pamp, 2008). However, factor solutions that suggest more than two subscales regularly result in subscale scores with unsatisfactory reliability (Cronbach's alphas < .70; see also Pincus et al, 2009).…”
Section: Multidimensional Perfectionism and Narcissismmentioning
confidence: 99%
“…However, factor solutions that suggest more than two subscales regularly result in subscale scores with unsatisfactory reliability (Cronbach's alphas < .70; see also Pincus et al, 2009). Hence we followed Corry et al's (2008) two-factor solution differentiating exhibitionism/entitlement ("I am apt to show off if I get the chance") and leadership/authority ("I see myself as a good leader"), which has demonstrated satisfactory reliability and validity (e.g., Corry et al, 2008).…”
Section: Multidimensional Perfectionism and Narcissismmentioning
confidence: 99%
“…Similarly, Foster and Campbell (2007) failed to reach the adequate reliability levels in many dimensions of the NPI. Similar to these studies, Corry et al, (2008) obtained a two-factor structure in their explanatory factor analysis of NPI. Although NPI has been used in many different studies, many of the dimensions of GNS in these studies have not reached adequate levels of reliability.…”
Section: Discussionmentioning
confidence: 49%
“…NPI, which is one of the limited measuring instruments in the literature which shows the seven dimensions that express the theoretical sub-structure of narcissism at the level of sufficient validity and reliability, has been used in many subsequent studies but has failed to reach the sufficient validity and reliability level (Corry et al, 2008;del Rosario and White, 2005;Foster and Campbell, 2003). Foster et al, (2015) suggested that the solution of this problem lies in the creation of completely new items.…”
Section: Introductionmentioning
confidence: 99%